Assessment of radioactivity in nuclear facilities (English for specific purposes) study aid - Rikhvanov, L. P. Professor of Tomsk Polytechnic University Doctor of geological- mineralogical sciences Honored geologist of Russia Honored Worker of higher professional education of the Russian Federation 1945-2020 (TPU Publishing House, 2023)
The main aim of the study aid is to show the need of the integrated approach to the assessment of the radioecological situation in the areas where the nuclear fuel cycle plants are located. Students will have an idea that the radiation environment is formed by both natural and the anthropogenic factors, and that radiation exist! everywhere and the radiation effect can be both negative and positive. The study aid is based on own research of professor L.P. Rikhvanov, as well as it is based on synthesis of the scientific works of scientists of Tomsk state university and Siberian State Medical university to assess the impact of activities of one of the largest nucleal fuel cycle enterprises in the world - Siberian Chemical Plant (SCP). This study aid is intended for Russian and foreign students and participants in courses and programms.